PEMBERDAYAAN KELOMPOK PEREMPUAN MELALUI PENGEMBANGAN USAHA RUMAHAN BERBASIS POTENSI LOKAL DI DESA PECATU - Putu Ratna Windusara Putri; Fahmi Tanjung; I Made Sujana; I Made Wisnu Wardana (Yayasan Nusantara Hasana Berdikari, 2023)
Women’s Empowerment Is An Important Strategy For Improving Family Welfare And Strengthening Rural Economies. Pecatu Village Possesses Various Local Potentials That Can Be Utilized For The Development Of Home-Based Businesses, Including Processed Food Products, Handicrafts, And Creative Products Based On Local Culture. However, Many Women’s Groups Still Face Challenges Related To Entrepreneurial Skills, Financial Management, Marketing, And Product Development. This Community Service Program Aimed To Strengthen The Capacity Of Women’s Groups Through The Development Of Home-Based Businesses Based On Local Potential. The Methods Employed Included Socialization, Entrepreneurship Training, Product Processing Workshops, Business Mentoring, And Program Evaluation. The Participants Consisted Of 35 Women Involved In Community Groups And Home-Based Business Activities In Pecatu Village. The Results Indicated Significant Improvements In Participants’ Knowledge And Skills Regarding Business Management, Simple Financial Recording, Product Development, And Digital Marketing Utilization. Furthermore, Participants Successfully Developed Systematic Business Plans Aimed At Increasing Household Income. The Program Positively Contributed To Enhancing Women’s Economic Independence And Supporting Community-Based Economic Development Through Local Resources.